Ownership of Co-creation Assets: Driving B2B Value Propositions in the Service Economy. (May 2018) - Ehret, Michael; Wirtz, Jochen
Abstract: The benefits of specialization have been driving the rise of the service economy and pushing capability frontiers and economic growth. In service economies, almost any activity, asset, and skill can be bought on competitive markets, making it harder to build competitive advantage on any of those inputs. Against that background, the question emerges what constitutes sustainable value propositions of service providers. Drawing on an emerging stream of research on the non-ownership value of services, we argue that service providers create value by taking on ownership of service assets and thereby transform uncertainty of value creation into economic opportunities. In our view, service providers offer the essential value proposition of transforming their clients' uncertainty downsides into opportunities related to assets such as vehicles, real estate, equipment and computing platforms. Clients benefit by delegating ownership of assets to the domain of a service provider. In turn, clients can focus their investment on their most promising assets. Service providers create sustainable competitive advantage by assuming ownership and excelling at the management of (a) unique physical assets, (b) unique intangible assets and (c) maintaining an appropriate architecture of social capital through customer relationships and business ecosystems.